Is the Climate Change being Real? A Case Study of College Students’ Climate Change Perception at Universiti Malaya - Kundariati, Maisuna; Ibrohim, Ibrohim; Rohman, Fatchur; Abdul Razak, Sarah; Nida, Safwatun (Journal of Environmental and Science Education, 2025)
Climate change is a socio-scientific issue which affecting to human life. Climate change was induced by the human activities (anthropogenic). People perception toward climate change might important to taking action address to climate change. This paper aim to analyze horticulture class students’ perception toward the climate change. Using a survey method, this study conducted in Biology Institute, Universiti Malaya, Malaysia. Fourthly students who enroll horticulture class declare be willing to participate in the study. The questionnaire consists of 25 questions reality (Q1-Q5), causes (Q6-Q10), valence of consequences 9 (Q11-Q14), spatial distribution (Q15-Q19), and temporal distribution (Q20-Q25). Data collection using a questionnaire in the form of a google form that was done for 30 minutes. The study find that students believe climate change is a serious problem in Malaysia region. Students also believe that climate change caused by human activists rather than natural phenomena. Climate change have already felt now and impacting local region and worldwide. This climate crisis giving a massive change in human lifestyle. In suggestion, all people around the world should take actions to tackling the climate change, both mitigation or adaptation ways. Mitigation and adaptation strategies needed to limiting the impact of climate change.